Early Adolescents' Experiences During the COVID-19 Pandemic and Changes in Their Well-Being - Gadermann, Anne; Thomson, Kimberly; Gill, Randip; Schonert-Reichl, Kimberly A.; Gagné Petteni, Monique; Guhn, Martin; Warren, Michael T.; Oberle, Eva (Frontiers in Public Health, 2022)
Background Early adolescence is a time of psychological and social change that can coincide with declines in mental health and well-being. This study investigated the psychological and social impacts of the COVID-19 pandemic from the perspective of students who responded to a survey in Grades 7 and 8 (ages 12–14) in British Columbia (BC), Canada. The objectives of this study were (i) to provide an overview on early adolescents' experiences and social-emotional well-being during the pandemic; and (ii) to examine whether changes in social experiences as well as feeling safe from getting COVID-19 at school were associated with changes in well-being outcomes over the course of a year. Methods A sample of n = 1,755 students from a large public school district self-reported on their life satisfaction, optimism, and symptoms of sadness across two time points: First, in their Grade 7 year (pre-pandemic; January to March, 2020) and then 1 year later in their Grade 8 year (during the pandemic; January to March, 2021). In Grade 8, students also reported on pandemic-specific experiences, including changes in mental health, social relationships, and activities, as well as coping strategies and positive changes since the pandemic. Data were collected online using the Middle Years Development Instrument (MDI), a population-based self-report tool that assesses children's social-emotional development and well-being in the context of their home, school, and neighborhood. Multivariable linear regression analyses were used to examine associations between pandemic-related changes in relationships and perceived safety from getting COVID-19 at school with changes in well-being outcomes. Results Students reported a range of experiences, with a large proportion reporting moderate concerns and impacts of the pandemic, including worries about their mental health and missing school activities. Students reported significantly lower optimism, lower life satisfaction, and higher sadness compared to the previous year. Within the sample, improvements in relationships with parents and other adults at home was associated with higher well-being during the pandemic. Implications Results from this study can inform decision making of policy-makers, educators, and practitioners working with youth, by providing information on students' experiences during the pandemic and identifying factors that may be protective for students' mental health during and beyond the pandemic.